Agronomic characterization of strawberry cultivars in substrate during late planting period in organic production system - Costa, Alessandro; Lima, Cláudia Simone Madruga; Souza, Leonardo Lucio Antonowicz de; Carloto, Cacea Furlan Maggi; Leandrini, Josimeire Aparecida; Pereira, Manuela Franco de Carvalho da Silva (Revista de Ciências Agroveterinárias, 2024)
The cultivation of strawberries in substrate is on the rise, and as a result, many aspects related to management have been modified, including the planting season for strawberries. Therefore, the objective of this research was to agronomically characterize strawberry cultivars in substrate during the late planting period in an organic production system. The evaluated cultivars were ALPINA10 and CAV 56.9 (day-neutral) and CAV 107.7 and CAV 107.12 (short-day). An experimental design was used in split plots, with three replications for each genotype. Evaluations included phenological aspects, plant characteristics, and production. Plants of the ALPINA10 cultivar exhibited late behavior in all evaluated phenological aspects. ALPINA10 showed greater vegetative and productive growth compared to CAV 56.9. On the other hand, CAV 107.12 exhibited more robust growth than CAV 107.7. For late planting conditions, the day-neutral cultivar ALPINA 10 and the short-day cultivar CAV 107.12 showed greater vegetative growth and production. However, due to the planting period, the values for all researched cultivars are lower, indicating that late planting is not recommended.